La collezione Erpetologica del Museo di Zoologia e Anatomia comparata dell’Università di Torino - Cei, José Miguel Alfredo María (1989)
The high importance of the zoological collections in the museums is pointed out, with particular attention to the collections of Reptiles and Amphibians. These animals, characterized by an ancient evolution, both with many stenoic, endemic and adapted to different environmental situations species, can offer useful zoogeographical and ecological informations on areas difficult to reach or seriously endangered by human activities. The large collections of the Zoological museum of the University in Turin are briefly illustrated. They include some very rare materials from South America, Africa, Oriental Region, the middle Asia and the mediterranean Area. The historical importance of this collection is also made evident.